Halal Sunscreens: Halal Awareness, Quality, Price, and Muslim Consumer Choice - Lathifah Khairunnisa (Journal of Economics and Business, 2025)
This study aims to analyze the factors that influence buying interest in halal sunscreen products for generation Z in central java. Primary data was obtained form questionnaires distributed online via google form. The sample collected was 100 respondents who had bought sunscreen products that had been certified halal. The analytical tool in this study used IBM SPSS Statistics 27 with multiple linear regression analysis. The results show that the variables of halal awarenesss, product quality, dan price perception have a positive and significant effect on the interest in halal sunscreen products. The suggestion of this research is for companies engaged in the beauty and medicine industry to pay attention to halal certification on sunscreen products and develop better quality sunscreen products and can educate consumers regarding this quality. Companies can also provide discounts or other competitive pricing strategies to increase buying interest in generation Z